Pediatric Infective Endocarditis: Has Staphylococcus aureus Overtaken Viridans Group Streptococci as the Predominant Etiological Agent? - Aisha Alshammary; Marilou Hervas-Malo; Joan L Robinson (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Viridans group streptococci (VGS) have traditionally been the most common etiological agents of infective endocarditis (IE). Advances in cardiovascular surgery and the increasing use of long-term central venous catheters may have altered the epidemiology of pediatric IE.